Feedback regulation between histone lactylation and ALKBH3-mediated glycolysis regulates age-related macular degeneration pathology - Ying Wang; Yi-Chen Zhang; Zi-Qin Ding; Shi-Yao Xu; Ye-Ran Zhang; Hong-Jing Zhu; Chang Huang; Jia-Nan Wang; Meidong Zhu; Jiang-Dong Ji; Biao Yan; Qing-Huai Liu; et al. (Proceedings of the National Academy of Sciences, 2025)
Age-related macular degeneration (AMD) is a leading cause of blindness among the elderly. It is characterized by degeneration of the retinal pigment epithelium (RPE), which can develop into choroidal neovascularization (CNV) to cause severe and rapid vision loss. Preventing this progression might help save vision, but the exact mechanisms remain unclear. In this study, using clinical AMD samples and the gene knockout mice, we reported that the m 1 A eraser ALKBH3 reshaped retinal metabolism to promote this progression. In RPE, the dm 1 ACRISPR system demonstrated that ALKBH3 demethylated the rate-limiting glycolytic enzyme HK2 to activate glycolysis, resulting in excess lactate production. This lactate promoted histone lactylation at H3K18, which in turn bound to ALKBH3 to amplify its transcription, establishing a positive feedback loop. The ALKBH3 inhibitor HUHS015 disrupted this loop, effectively mitigating RPE degeneration. Furthermore, ALKBH3 directly targeted the proangiogenic factor VEGFA to modulate the metabolic cross-talk between RPE and choroidal capillaries, thus promoting CNV. HUHS015 inhibited CNV synergistically with the anti-VEGF drug Aflibercept. Overall, our study provides critical insights into the molecular mechanisms and metabolic events that facilitates the progression from RPE degeneration to CNV in AMD, laying the groundwork for new treatments of age-related retinal disorders.